2022
DOI: 10.3389/fcvm.2022.1012220
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital arrhythmic burden reduction in diabetic patients with acute myocardial infarction treated with SGLT2-inhibitors: Insights from the SGLT2-I AMI PROTECT study

Abstract: BackgroundSodium-glucose co-transporter 2 inhibitors (SGLT2-i) have shown significant cardiovascular benefits in patients with and without type 2 diabetes mellitus (T2DM). They have also gained interest for their potential anti-arrhythmic role and their ability to reduce the occurrence of atrial fibrillation (AF) and ventricular arrhythmias (VAs) in T2DM and heart failure patients.ObjectivesTo investigate in-hospital new-onset cardiac arrhythmias in a cohort of T2DM patients presenting with acute myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…However, SGLT-2 inhibitors do not affect the risk for ventricular arrhythmias and sudden cardiac death, as reported in another recently published meta-analysis [52]. In the acute setting of myocardial infarction, it was recently demonstrated that prior use of SGLT-2 inhibitors among the affected subjects resulted in significantly lower rates of atrial fibrillation, ventricular tachycardia and ventricular fibrillation, while SGLT-2 inhibitor use was associated with a significant reduction in the odds for new-onset arrhythmia during hospitalization by 65% [53].…”
Section: Arrhythmic Burdenmentioning
confidence: 76%
“…However, SGLT-2 inhibitors do not affect the risk for ventricular arrhythmias and sudden cardiac death, as reported in another recently published meta-analysis [52]. In the acute setting of myocardial infarction, it was recently demonstrated that prior use of SGLT-2 inhibitors among the affected subjects resulted in significantly lower rates of atrial fibrillation, ventricular tachycardia and ventricular fibrillation, while SGLT-2 inhibitor use was associated with a significant reduction in the odds for new-onset arrhythmia during hospitalization by 65% [53].…”
Section: Arrhythmic Burdenmentioning
confidence: 76%
“…Furthermore, malignant outcomes are worse if VT/VF occurs late instead of early [5,11]. Fortunately, the recent investigation shows the use of sodium-glucose co-transporter 2 inhibitors (SGLT2-i) was associated with a lower risk of new-onset arrhythmic events, especially VT/VF, during hospitalization and long-term follow-up for AMI patients complicated T2DM [14,15]. Therefore, the difference in the effect of VT/VF on the prognosis of STEMI shows the varied electrophysiological mechanisms of VT/VF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the NLR could be reduced by anti-inflammatory therapy using canakinumab [ 20 ]. Another promising pharmacological agent, sodium-glucose cotransporter 2 inhibitor, could also decrease the level of NLR by directly targeting inflammatory pathways such as nucleotide-binding domain-like receptor protein-3 inflammasome [ 21 , 22 ]. Recent evidence suggested that inflammation indices could identify high-risk patients with thromboembolic diseases such as acute pulmonary embolism or peripheral arterial disease [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%